Street Children and Mobile Youth Work in Africa - the 8th ISMO Symposium October 2003 - Walther Specht (Social Work and Society, 2004)
The International Society for Mobile Youth Work (ISMO) and the National Council of Churches in Kenya (NCCK) organised from the 27th to 30th October 2003 at the Jumuia Conference and Country Home in Limuru/Kenya with 198 participants from 35 countries around the world the 8th International Symposium on Mobile Youth Work with special focus on children at risk (street children and youth) in Africa. For this purpose there were invited field workers, scientists and stakeholders engaged as advocates for the rights and well being of endangered children and youths. The participants came mainly from African countries and of course especially from Kenya, but also from Asia, Latin America and from Europe.